ENVIRONMENTAL SURVEILLANCE ANDO CONTROL ACTIONS FOR DENGUE PREVENTION: A CASE STUDY IN THE ALTO URUGUAI GAÚCHO REGION, RIO GRANDE DO SUL STATE, BRAZIL - Salomoni, Saionara Eliane; Bald, Marlene; Andreolla, Neusa; Fontaneli, Roberto Serena; Barasetti, Cidinei César; Vilanova, Rafaela Lima Kurtz; de Amorim, Tamires Correa (Editora Impacto Científico, 2025)
Dengue is an acute febrile disease of viral etiology, presenting as benign in its classic form and severe in its hemorrhagic form. It is the most significant arboviral disease, posing a serious global public health issue in tropical and subtropical countries where environmental conditions favor the proliferation of Aedes aegypti. In Brazil, dengue arrived in the 18th century. Most of the population lives in urban areas, where challenges include ensuring regular water supply, adequate waste collection and disposal, and addressing climatic conditions. This study aims to examine the routine actions of endemic agents, considering the number of identified cases, Aedes aegypti mosquito breeding sites, and the current epidemiological status of the disease in the Alto Uruguai region of Rio Grande do Sul between 2019 and 2024. Dengue cases in Alto Uruguai Gaúcho increased in 2021, 2022, and 2024, likely due to elevated temperatures and rainfall, which contributed to a rise in mosquito breeding sites and consequently more infections. Therefore, it is essential to enhance actions such as waste collection drives and educational campaigns for dengue prevention and control, as public awareness and cooperation are crucial for managing the disease.DOI: https://doi.org/10.56238/edimpacto2025.060-018